(3JGQjN GdSGOI GdYdeGA Gdced GdfHdGA GdaVdGA (B( (3Hfi GdhRjQ(B)s - (3CMeO Hf YHO Gddg Hf CMeO Hf EHQGgje Hf Ydj Hf GdeQJVj, GHf GdhRjQs
(3BNQgG (B:s
(3bGd ai GdCe(B: (3Je Pdc efbhdkG HdaXI ef GdfSNI GdCUdjg hdYdgG GdeShOI, hajgG eHjVGJ ai ehGVY YOI s
(3fSNI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B73 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs